Experimental Study and Numerical Analysis on Impact Resistance of Civil Air Defense Engineering Shear Wall. (17th December 2021) - Shi, Chenglong; Zhang, Jigang; Zhang, Junbo; Shao, Feng; Zhang, Yicong; Zhang, Menglin
Abstract : In order to study the impact resistance of civil air defense engineering shear wall, the impact resistance of civil air defense engineering shear wall was studied by combining finite element numerical simulation with pendulum impact test. The effects of impact height, pendulum mass, and impact times on the impact resistance of civil air defense engineering shear walls were analyzed. It was shown that when the impact height increased from 0.4 m to 2.5 m, the failure mode of civil air defense engineering shear wall tended to be local impact failure, and the horizontal displacement in the middle of the wall span increased. The concrete crushing occurred in the impact area of the back of the civil air defense engineering shear wall. The increase in the impact height is a negative factor for the impact resistance of the civil air defense engineering shear wall. With the increase of pendulum weight, the number of concrete horizontal cracks in the back of the civil air defense engineering shear wall increased, while the number of vertical cracks decreased, but the impact surface was destroyed. Through multiple impact tests on the civil air defense engineering shear wall, the civil air defense engineering shear wall had accumulated damage. The longitudinally loaded steel on the back reached the ultimate strength, and there are large cracks at the bottom and even collapses. The increase of impact times has a great influence on the impact resistance of the civil air defense engineering shear wall. Through the analysis of the factors affecting the impact resistance of civil air defense engineering shear wall, it provides guidance for civil air defense engineering shear wall to resist impact load.